Trapped ion mobility spectrometry and PASEF enable in-depth lipidomics from minimal sample amounts - Catherine G. Vasilopoulou (Nature Portfolio, 2020)
Trapped ion mobility (TIMS)-mass spectrometry with parallel accumulation-serial fragmentation (PASEF) facilitates high-sensitivity proteomics experiments. Here, the authors expand TIMS and PASEF to small molecules and demonstrate fast and comprehensive lipidomics of low biological sample amounts.